Case report: Gross persistent rectal prolapse. A case treated without mesh using deep retrorectal dissection/suturing - Miyano, Go; Yamada, Shunsuke; Murakami, Hiroshi; Lane, Geoffrey J.; Yamataka, Atsuyuki (Frontiers in Pediatrics, 2022)
Gross rectal prolapse (GRP) in a previously well 15-year-old male is presented to illustrate technical challenges and planning for surgical intervention for optimal treatment and improvement in quality of life (QOL). The patient presented with a history of full-thickness rectal prolapse of increasing severity and incidence over 6 months that occurred with every bowel motion, varying from 10cm to 40cm. The patient was adept at reducing the prolapsed rectum after each motion. On preoperative barium enema, inversion of the anal verge was identified with prolapse of the rectum. The patient was placed in a Trendelenburg position and under general anesthesia, four ports were inserted. The peritoneum was incised and blunt dissection used to expose the levator ani complex (LAC) taking care to prevent lateral nerve injury and preserve regional vascularity. Seven polypropylene sutures were used to fix the seromuscular posterior wall of the rectum to the median raphe of the LAC, the presacral fascia, and the periosteum of the sacral promontory. Operative time was 170 minutes. Postoperative recovery and progress were unremarkable. Currently, after 5 years follow-up, defecation is regular and normal without recurrence of prolapse. For prolapse involving protrusion of the upper rectum without inversion of the anal verge, rectal fixation to the sacral promontory without further dissection beyond the peritoneal reflection is adequate, but when extensive prolapse is associated with inversion of the anal verge, more extensive repair is required. More extensive blunt dissection from the peritoneal reflection to the LAC with multiple rectopexy sutures is a valid option for reducing risks for recurrence, and eliminate mesh-related complications.